CALISTUNG: URUTAN PEMBELAJARAN BAHASA MULAI DARI SD KELAS RENDAH - Irsanti, Kurnia; Umi Kalsum; Nazurty; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Calistung learning in low-grade primary schools plays an important role in improving students' language and communication skills. This article discusses the sequence of language learning starting from the lower primary grades, which includes reading, writing and counting. Reading is the initial stage of language learning, which includes the recognition of letter shapes, recognition of linguistic elements, and slow reading speed. Writing as a medium of student communication so that students can convey their ideas, ideas, and feelings to each other through a series of words. Counting as a very important ability for students after reading and writing, which needs to be developed in equipping students. Thus, the sequence of language learning starting from low grade elementary school has important significance in improving students' language abilities and communication skills.